Variations of PM2.5 sources in the context of meteorology and seasonality at an urban street canyon in Southwest Germany - Song, Junwei; Saathoff, Harald; Gao, Linyu; Gebhardt, Reiner; Jiang, Feng; Vallon, Magdalena; Bauer, Jonas; Norra, Stefan; Leisner, Thomas (Atmospheric environment, 2022)
In order to assess the factors controlling urban air pollution, we characterized fine particulate matter (PM2.5) at an urban street canyon in southwest Germany, in summer 2019 and winter 2020. The average mass concentration of PM2.5 was higher in dry and hot summer (7.0 ± 3.5 μg m−3) than in cold and humid winter (5.8 ± 2.8 μg m−3) with frequent wet scavenging. The non-refractory PM2.5 (NR-PM2.5) measured with an aerosol mass spectrometer (AMS) plus black carbon (BC) mostly consists of organic aerosol (OA) with 60% in summer and 44% in winter. The contributions of sulfate to NR-PM2.5 plus BC was higher in summer (18%) than in winter (13%), while that of nitrate was lower in summer (6%) than in winter (22%). During the entire measurement periods in both seasons, relatively flat diurnal variations of sulfate were found, suggesting that it was associated with regional transport. However, occasionally rapid increase of sulfate can be caused by the transport of upwind industrial sources and enhanced vertical mixing processes. Nitrate showed a peak at morning rush hours related to traffic emissions, and then subsequently decreased by evaporation processes during daytime with higher temperature. Positive matrix factorization analysis revealed that the total OA was dominated by secondary organic aerosol (SOA) over the primary traffic emissions with ∼82% in summer and ∼48% in winter. A detailed analysis of two pollution episodes clearly demonstrated the impact of meteorological conditions on secondary aerosol formation and accumulation. A summertime heatwave episode showed high contributions of SOA to PM2.5 mass, which formed locally through daytime photochemical oxidation as well as nighttime chemistry of biogenic precursors. A wintertime transitional episode occurred with significant shift from relatively warm and humid to cold and dry conditions. The fast formation of sulfate, nitrate, ammonium and SOA were found under the warm and humid period after receiving a local industrial emission plume. The cold and dry period was influenced by various sources including long-range transport of Saharan dust and anthropogenic emissions in central Europe. This study highlights the variations of urban PM2.5 sources under certain meteorological conditions such as summer heatwave and humid winter, which are expected high occurrence in future. Our results provide the implication on actual needs of mitigation actions to these pollution episodes in less-polluted western Europe cities.